Esophageal submucosal gland duct adenoma: a clinicopathological and immunohistochemical study with a review of the literature. Issue 8 (6th November 2015) - Nie, L.; Wu, H. Y.; Shen, Y. H.; Fan, X. S.; Sun, Q.; Huang, Q.; Chen, J.
Summary: Esophageal submucosal gland duct adenoma (ESGDA) is a rare tumor. The clinicopathological features of the ESGDA and its precursor lesion have not been comprehensively evaluated. In this study, we aimed at delineating the clinicopathological features of the ESGDA and cyst formation of the esophageal submucosal gland duct (ESGD), as well as their correlations and clinical implications. We identified three cases of ESGDA and 16 cases of cyst formation of the ESGD among 786 endoscopic mucosal resection specimens over a 7‐year period. The median patient age was 58 years with a male predominance. These lesions were small submucosal bulges locating at the lower esophagus with a size no more than 1 cm. The main microscopic changes of these lesions included content retention, multilayered epithelium or papillary folds of the ESGD and inflammatory cell infiltration, acidophilic degeneration, hyperplasia or atrophy of the acini. The included cases generally showed moderate to severe microscopic esophagitis. The ESGDA was mainly consisted by multiple glandular cysts covered by two layers of cells. Immunohistochemical results showed that the luminal duct lining cells and basal cells were positive for CK7 and p63, respectively. Both of the two layer cells were positive for HMWCK and negative for CK20, p53, CDX2, MUC5AC, MUC6, MUC2 and MUC1. The proliferation index was very low (1%). The diagnostic criteria of the ESGDA were proposed and, the differential diagnosis was discussed. Cyst formation of the ESGD is considered to be the precursor lesion of the ESGDA, because they have overlapping clinicopathological features with progressive relationship. In addition, the ESGDA have close connection with advance of the GERD and, probably, an increased risk of carcinoma.